The Effect of Comic-Based Realistic Mathematics Approach on Improving Skill of Students’ Concept Understanding - Sipayung, Tetty Natalia; Simanjuntak, Sinta Dameria; Wijaya, Ariyadi; Sugiman, Sugiman (International Journal of Trends in Mathematics Education Research, 2023)
Learning that involved the daily life accompanied by interesting learning media can be used as an option to help students in learning, particularly in improving students' concepts understanding. It is possible to do by utilization of familiar media that are generally liked by students. One of them is comic. Therefore a research about learning by comic based realistic mathematical approach was carried out in order to find out its effect on improving the skills of students concepts understanding on fraction material. This study is a quasi-experimental research. The population of study are 7th grade students of SMP RK Serdang Murni Lubuk Pakam on Academic Year 2019/2020. The first class that consist of 31 students are categorized as the control class and the second class consist of 32 students are experimental class. The pre-test and post-test questions were provided as an instrument of study. The data were analyzed using the Anova and Welch Brown-Forsythe tests to proof the hypotesis. Moreover, normality test with Liliefors test and the homogeneity test with the Levene’s test. The results of this study stated that learning with comics-based realistics mathematical approach has a significant effect on improving the skills of students concept understanding.